Notaries’ Roles in Land Rights Transfers: Balancing Deed Formality with Substantive Legal Protection Responsibilities and Accountability - Saiful Islam; La Ode Husen; Anggreany Arief (Manunggal Halim Jaya, 2026)
This study examines the role and responsibility of notaries in the transfer of land rights, focusing on the tension between formal compliance in authentic deeds and the realization of substantive legal protection. The objective of this research is to critically analyze whether the current formalistic framework of notarial authority is sufficient to ensure legal certainty and justice, and to propose a reconceptualization of notarial duties that integrates both procedural and substantive dimensions. The research employs a normative legal method, utilizing statutory and conceptual approaches to analyze relevant legislation, legal doctrines, and scholarly perspectives concerning notarial functions and land law. Data are analyzed using a descriptive prescriptive technique to both explain existing legal norms and formulate normative recommendations. The findings reveal that the prevailing practice of notarial duties remains heavily oriented toward formal validity, often reducing the notary to a passive recorder of parties’ intentions. This formalistic approach, while ensuring procedural legality, has proven inadequate in preventing disputes arising from fraud, misrepresentation, and unequal bargaining power. The study identifies a significant gap between formal authenticity and substantive justice, particularly in land transactions that carry high economic and social consequences. This research finds that the concept of substantive authenticity offers a viable framework to bridge this gap, requiring notaries to exercise due diligence, ensure informed consent, and actively verify the material aspects of transactions. The study concludes that strengthening the notarial role through a more substantive approach is essential to enhance legal protection, prevent disputes, and uphold justice within the land law system.